Public finance management reform and expenditure control in Ghana: the role of the ministry of finance in implementing the MTEF - Acheampong, Michael Ekow (Department of Political Studies, 2020)
Public expenditure control is vital in countries because it is a key instrument for ensuring effective government strategic planning and policy priorities. In many countries, public expenditure control has been inadequately implemented because of weak accounting systems, a weak cash management system and a weak flow of information, among others, despite public finance management reforms implemented in developing countries. Public expenditure management has been a concern in Ghana's public service because of weak budget formulation, weak monitoring and evaluation, and an ineffective flow of information between the ministry of finance (MOF) and the key public institutions. The Medium-Term Expenditure Framework (MTEF) has been introduced in Ghana's public service but it has been faced with challenges after the initial stage of implementation of the reforms. This study sought to examine why public finance management reforms appears to have failed to control public expenditure in Ghana, by investigating the ministry of finance's (MOF) role in implementing the MTEF. The study employs a qualitative method using interviews with officials from the MOF to examine the role of the MOF in implementing the MTEF. The key themes that the researcher sought to test through the research as potential factors behind poor expenditure control included the coordination amongst other government institutions, weak planning and forecasting, monitoring and evaluation capacity, information management systems and cash management systems, the political environment and the commitment control. The findings revealed that, despite the importance of political environment and the commitment control, planning and forecasting, the monitoring and evaluation capacity, information management system and the cash management and the coordination management government institutions in implementing the MTEF by the MOF, the new public management framework is not well implemented as it should be. The findings also revealed that in implementing the MTEF by the MOF, coordination among other government institutions such as the MOF and the NDPC has been improved and overcoming the shortcoming of implementing the public finance management reform in Ghana.